Interview with Dr. Yi-Wei Chen: education is the main method to popularize BNCT, a powerful special cancer treatment - Chu, Yuchun (Therapeutic Radiology and Oncology, 2018)
The 3rd Annual Academic Conference of Taiwan Society of Neutron Capture Therapy (Jointly with the 10th Trilateral BNCT meeting between Taiwan and Japan) was held in Taipei Medical University Hospital in Taiwan on January 27th, 2018. Experts from Taiwan and Japan exchanged their opinions and discoveries related to Boron Neutron Capture Therapy (BNCT) on the forum.